Living a calling and work engagement: JD-R approach - Low, Eng Wah (2021)
This study examined Job Demands-Resources model to predict burnout and performance (Bakker, Demerouti, & Verbeke, 2004) and also Burnout and work Engagement: the JD-R approach (Bakker, Demerouti, & Sanz-Vergel, 2014) to investigated the influence of living a calling to work engagement and work-related burnout by examining propositions from Work as Calling Theory (Duffy, Dik, Douglass, England, & Velez, 2018). A total of six hypotheses was developed for our study, three of the hypotheses to test job demands, emotional demands and living a calling and their effects on work related burnout; while the other three hypotheses test job demands, emotional demands and living a calling on work engagement. Our survey conducted provided the empirical support for our hypotheses. Our study found close relationship of job and emotional demands having a positive relationship to work related burnout which is aligned with JD-R model. We also found that both emotional demand and living a calling are psychological aspect for the employee which has direct relationship to work engagement.